Equal Rights To Receive Legal Protection For Justice Collaborators (Bharada Richard Eliezer Case Study) - Sitompul, Brisky Septian; Bambang Waluyo (Journal of Law, Politic and Humanities, 2024)
This research project attempts to learn more regarding the Justice Collaborator and the progression of the Brigadier Yosua homicide investigation. This study utilizes prescriptive study findings, which addresses legal disputes that have come up and created disturbances in ordinary aspects of a community by using the provisions of beneficial law, or regulations, as the main frame of guidance. Officially identified as a judicial partner, Bharada E expects that the magistrate will take this consideration in the soon tobe conducted trial surrounding the FS-alleged killing or murder of Brigadier Yosua Hutabarat. Bharada E was granted the status of judicial associate for being willing to assist the justice system with determining the matter based on the truth of the matter. In order to provide crime for every party mindful of the use using justice accomplices seeks to reveal criminality networks, the people within them, and their reasons for the offenders. Another tactic utilized by the government to strengthen the disincentive impact on violators is to impose remitted requirements.